Study on specific species of malaria in relation to haematological changes - Dr. Binita Kanaujia; Dr. Anand AS.; Dr. Sagar Mhetre (Tropical Journal of Pathology and Microbiology, 2021)
Background: As malaria is a potential medical emergency, prompt and accurate diagnosis is critical for its effective management. Conventional microscopic examination of peripheral thick and thin blood smear examination remains the “gold standard” for malaria diagnosis. Material: A 2 year prospective study from 2011 to 2013 was conducted at Navodaya Medical College Hospital and Research Centre, Raichur. The study comprised of a total number of 150 cases positive for Malaria, collected from above mentioned centre and those referred from peripheral referral centres. Clinical history regarding age, sex, nature and duration of illness were elicited. Blood sample for haematological study was taken before starting anti-malarial drugs in all these cases. Result: Out of total cases, P. vivax infected cases (62%) were common than P. falciparum (34%) and mixed infection cases [PV & PF] (4%). Most common presenting symptom of cases affected by PV, PF and mixed infection were fever and chills & rigors and least common symptom was cough. Most important haematological changes observed were anaemia and thrombocytopenia (77.3% each) and leucopenia (31.3%). All the above mentioned changes in haematological parameters were species specific and statistically significant, except for red cell indices, DLC and ESR. Conclusions: In conclusion, changes in haematological profile can help in early diagnosis of specific species of malaria for timely and appropriate treatment that can reduce the severity and prevention of additional consequences.